Fiscal Decentralization and Poverty Paradox in Papua: Governance Failures under Special Autonomy - Salmawati salmawati; Miryam Diana Kalagison; Haliza Ayswhara (Journal of Government and Civil Society, 2026)
This study aims to analyze the influence of the Special Autonomy Fund (Otsus) and local economic growth on poverty levels in Papua. The study uses a Mix method approach, namely quantitative data with survey methods, Questionnaires and reports on the realization of the Special Autonomy Fund and qualitative data namely interviews. Data analysis techniques include correlation tests and multiple linear regression. The results of the study indicate that Regional Economic Growth is Significantly Correlated with Poverty Alleviation The results of the Pearson correlation test (r = 0.765; p < 0.05) indicate that regional economic growth has a strong and significant relationship with poverty alleviation, the Special Autonomy Fund (Otsus) Has a Significant Impact But Is Not Yet Effective in Poverty Alleviation The results of simple regression show a positive coefficient (B = 0.532), the R Square value is only 25.8%, so the Special Autonomy Fund is only able to explain a quarter of the variation in poverty, while 74.2% is influenced by other factors (human resources, governance, infrastructure, income distribution). The Special Autonomy Fund and local economic growth simultaneously significantly influence poverty reduction, with an R value of 0.856 and an R Square of 0.873, meaning 87.3% of the poverty variable can be explained by these two variables. The Durbin-Watson value of 2.112 indicates no autocorrelation in the model. Partially, the Special Autonomy Fund has a positive and significant effect on improving access to public services and community income, while local economic growth also strengthens poverty reduction. Meskipun lebih dari dua dekade implementasi Otonomi Khusus (Otsus) dan pencairan lebih dari Rp 138,65 triliun, tingkat kemiskinan Papua tetap berada di angka 26,03–34,26% jauh di atas rata-rata nasional menampakkan paradoks mendasar antara desentralisasi fiskal skala besar dan hasil pembangunan inklusif. Studi yang ada telah menilai efektivitas Otsus terutama pada tingkat makro-fiskal, mengabaikan kualitas tata kelola sebagai variabel mediasi yang penting. Studi ini mengatasi kesenjangan tersebut dengan meneliti bagaimana dana Otsus dan pertumbuhan ekonomi lokal secara bersamaan memengaruhi kemiskinan di Papua, menggunakan desain penjelasan sekuensial metode campuran yang menggabungkan regresi linier berganda (n=240) dengan wawancara kualitatif sistematis terhadap informan kunci. Temuan menunjukkan paradoks struktural, peningkatan alokasi Otsus berkorelasi dengan kemiskinan yang lebih tinggi daripada lebih rendah (B=0,532, R²=0,258), suatu pola yang dijelaskan oleh penguasaan dana oleh elit, salah alokasi terhadap pengeluaran administratif dan konsumtif, dan dinamika pertumbuhan yang tidak inklusif. Secara gabungan, Otsus dan pertumbuhan ekonomi lokal menjelaskan 87,3% variasi kemiskinan (R²=0,873), namun pertumbuhan itu sendiri tetap tidak inklusif. Secara teoritis, studi ini menantang asumsi bahwa desentralisasi fiskal secara inheren mengurangi kemiskinan, menunjukkan bahwa kualitas tata kelola adalah kondisi mediasi yang kritis. Implikasi kebijakan menuntut reorientasi alokasi Otsus ke arah pemberdayaan ekonomi berbasis komunitas yang produktif, penganggaran berbasis kinerja, dan penguatan akuntabilitas kelembagaan.